2022
DOI: 10.1001/jamaneurol.2022.3413
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Angiotensin Receptor Blocker Therapy and Incidence of Epilepsy in Patients With Hypertension

Abstract: ImportanceArterial hypertension is associated with an increased incidence of epilepsy. Results from animal studies suggest that angiotensin receptor blocker (ARB) therapy could inhibit epileptic seizures. However, there is a lack of clinical data to support the use of ARB therapy in humans.ObjectiveTo assess whether ARB therapy is associated with a decreased incidence of epilepsy in patients with hypertension.Design, Setting, and ParticipantsThis cohort study obtained data from the Disease Analyzer database (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…A recent retrospecJve study showed significantly reduced epilepsy incidence in a cohort of arterial hypertension paJents from Germany who were being treated with six different angiotensin II receptor blockers (Losartan, Valsartan, Telmisartan, Olmesartan, Candesartan, Irbesartan). The same study showed that Losartan alone associated with a significantly lower incidence of epilepsy (DOEGE et al 2022). Losartan was also effecJve at reducing seizures and associated neuronal damage in a mouse model of hypertension and epilepsy (TCHEKALAROVA et al 2016).…”
Section: Neurod2 Crispant Tadpole Brains Appear Morphologically Norma...mentioning
confidence: 92%
“…A recent retrospecJve study showed significantly reduced epilepsy incidence in a cohort of arterial hypertension paJents from Germany who were being treated with six different angiotensin II receptor blockers (Losartan, Valsartan, Telmisartan, Olmesartan, Candesartan, Irbesartan). The same study showed that Losartan alone associated with a significantly lower incidence of epilepsy (DOEGE et al 2022). Losartan was also effecJve at reducing seizures and associated neuronal damage in a mouse model of hypertension and epilepsy (TCHEKALAROVA et al 2016).…”
Section: Neurod2 Crispant Tadpole Brains Appear Morphologically Norma...mentioning
confidence: 92%
“…In this study, 5 the authors tried to answer the questions by analyzing a large German insurance claims database covering 3% of all outpatient practices in Germany. The study was based on ICD-10 codes, and included adults with an International Classification of Diseases (ICD-10) code for hypertension and prescription of an antihypertensive agent; beta-blockers (BB), calcium channel blockers, angiotensin-converting enzyme inhibitors (ACEi), and angiotensin receptor blockers (ARB).…”
Section: Commentarymentioning
confidence: 99%
“…Losartan, an ARB medication, has been shown to block astrocyte activation and maintain the integrity of the blood brain barrier (BBB) in animal and human studies . A retrospective analysis of a health administrative database in Germany found a lower incidence of epilepsy in ARB users compared with other classes of antihypertensive medications . However, the study results have not been extrapolated to the US population.…”
Section: Introductionmentioning
confidence: 99%